ANALYSIS OF NUTRIENT STRESS IN THE GROWTH PHASE OF CHERRY TOMATOES (SOLANUM LYCOPERSICUM VAR. CERASIFORME) HYDROPONICALLY. - Ridho Victory Nazara; Eliyunus Waruwu; Putra Hidayat Telaumbanua; January Dawolo; Destriman Laoli (CV. Radja Publika, 2024)
One solution to urban farming is hydroponic cultivation. Currently, the development of the world of agriculture, especially in the field of hydroponics, is increasingly rapid. When compared to conventional farming, hydroponics has advantages that conventional farming does not have. One plant that is often cultivated hydroponically is the cherry tomato plant. The growth and production of tomatoes with a good hydroponic system requires the right concentration and volume of nutrients. This research used a non-factorial randomized block design (CRD) with Nutrient concentration (N) treatment, consisting of 5 levels, namely: N1 = 800 ppm, N2 = 900 ppm, N3 = 1000 ppm, N4 = 1100 ppm and N5 = 1200 ppm. The results showed that nutrient concentration had an effect on the generative growth phase, but had no significant effect on the vegetative growth phase of cherry tomato plants. Nutrient concentration influences the morphology and physiology of cherry tomato plants. Nutrient concentration had a significant effect on the production of cherry tomato plants hydroponically with the heaviest fruit weight per plant found in the AB Mix nutrient concentration of 1000 ppm (N3) of 97.89 g.